2015
DOI: 10.3844/ojbsci.2015.42.48
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Platelet Rich Plasma on Post Cryopreservation Viability, Morphology and Proliferation of Human Umbilical Cord Stem Cells

Abstract: In most cryopreservation medium, Fetal Bovine Serum (FBS) is used as supplement, while it is well known that FBS contains xenoproteins that can be incorporated into the cells and may be harmfull, as they can elicit immune response. Therefore, finding other xenofree materials as FBS alternative in cryopreservation medium is very important. Platelet Rich Plasma (PRP) is albumin rich and is a candidate for FBS alternative as cryopreservation supplement. Albumin is a natural extracellular cryoprotective agent that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…9 Our previous result showed that serial passages after cryopreservation in the same method as this research caused enlargement of cell size at P-2 compared to fresh cells (mean value 2674 vs 2056 µm 2 ), 11 though this study showed that in P-2 there was no senescent cells. Therefore, after cryopreservation, P-2 cells in this study might begin the senescent process, but had not accumulated enough β galactosidase to be detected with β galactosidase staining, which in our study, began to detect senescence in P-3.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…9 Our previous result showed that serial passages after cryopreservation in the same method as this research caused enlargement of cell size at P-2 compared to fresh cells (mean value 2674 vs 2056 µm 2 ), 11 though this study showed that in P-2 there was no senescent cells. Therefore, after cryopreservation, P-2 cells in this study might begin the senescent process, but had not accumulated enough β galactosidase to be detected with β galactosidase staining, which in our study, began to detect senescence in P-3.…”
Section: Discussionmentioning
confidence: 85%
“…Cell density at cryopreservation was 500,000 cells/mL, and cryopreservation procedure was done at -20 o C for 24 hours, and then moved into liquid N2 tank, vapor phase as described previously. 11 After one month, the cells were thawed and subjected to serial passages until P-8, and senescent analysis was done for all passages.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This research was conducted for 16 months, from August 2016 -October 2017. The samples of this study were mesenchymal stem cells from bone marrow isolated by the simple method by Pawitan et al [36] and mesenchymal stem cells from fat tissue isolated by the simple method belonging to the RSCM-FKUI UPT Stem Cell Laboratory [37] . All cells were cryopreserved in the first phase using the xeno-free cryopreservation method.…”
Section: Methodsmentioning
confidence: 99%